Transmission Clusters, Predominantly Associated With Men Who Have Sex With Men, Play a Main Role in the Propagation of HIV-1 in Northern Spain (2013–2018) - Gil, Horacio; Delgado, Elena; Benito, Sonia; Georgalis, Leonidas; Montero, Vanessa; Sánchez, Mónica; Cañada-García, Javier E.; García-Bodas, Elena; Díaz, Asunción; Thomson, Michael M.; , The Members of the Spanish Group for the Study of New HIV Diagnoses (Frontiers in Microbiology, 2022)
Viruses of HIV-1-infected individuals whose transmission is related group phylogenetically in transmission clusters (TCs). The study of the phylogenetic relations of these viruses and the factors associated with these individuals is essential to analyze the HIV-1 epidemic. In this study, we examine the role of TCs in the epidemiology of HIV-1 infection in Galicia and the Basque County, two regions of northern Spain. A total of 1158 HIV-1-infected patients from both regions with new diagnoses (NDs) in 2013-2018 were included in the study. Partial HIV-1 pol sequences were analyzed phylogenetically by approximately maximum-likelihood with FastTree 2. In this analysis, 10,687 additional sequences from samples from HIV-1-infected individuals collected in Spain in 1999-2019 were also included to assign TC membership and to determine TCs’ sizes. TCs were defined as those which included viruses from ≥4 individuals, at least 50% of them Spaniards, and with ≥0.95 Shimodaira-Hasegawa-like node support in the phylogenetic tree. Factors associated to TCs were evaluated using odds ratios (OR) and their 95% confidence intervals (CI). Fifty one percent of NDs grouped in 162 TCs. Male patients (OR: 2.6; 95% CI: 1.5-4.7) and men having sex with men (MSM) (OR: 2.1; 95% CI: 1.4-3.2) had higher odds of belonging to a TC compared to female and heterosexual patients, respectively. Individuals from Latin America (OR: 0.3; 95% CI: 0.2-0.4), North Africa (OR: 0.4; 95% CI: 0.2-1.0), and especially Sub-Saharan Africa (OR: 0.02; 95% CI: 0.003-0.2) were inversely associated to belonging to TCs compared to native Spaniards. Our results show that TCs are important components of the HIV-1 epidemics in the two Spanish regions studied, where transmission between MSM is predominant. The majority of migrants were infected with viruses not belonging to TCs that expand in Spain. Molecular epidemiology is essential to identify local peculiarities of HIV-1 propagation. The early detection of TCs and prevention of their expansion, implementing effective control measures, could reduce HIV-1 infections.